Das glebas aos continentes: um diálogo sobre indicadores socioambientais - Peron, Darci (2010)
This study has been carried out in a rural settlement of the Agrarian Reform National Institute Wesly Manoel dos Santos, also known as Gleba Mercedes V, located in the municipal district of Sinop, Mato Grosso. It involves elements for the analysis of Human Welfare of people settled there, through three socio-environmental indicators: the Ecological Footprint, the Human Development Index and the Happiness Index. Based on the case study methodology, this research triangulates quantitative and qualitative data and it uses the following methods: 1- the Ecological Footprint Method through the variables: water consumption, power, fuel and wastes generation; 2- the Happy Planet Index Method, which relates Happiness to the Ecological Footprint, in which the program: Statistical Package for Social Sciences (SPSS) has been used, in order to systematize the gathered data; and 3- Method adopted by PNUD to check the Human Development Index, through the variables of longevity, education and health. Through these collected data and the figures found for the three magnitudes: Ecological Footprint, Happiness Index and Human Development Index, we have examined the impacts brought about by the activities put into practice by the inhabitants of that community in the natural environment, life pattern of the inhabitants and their happiness, trying to assess the human welfare condition of the community dwellers, aiming to evaluate the sustainability degree of the referred settlement. Using a previously structured questionnaire we could assess the satisfaction level towards life, which is 5.62 (in a 0 to 10 scale). Based on the Happy Planet Index Method, through the relationship between the local Ecological Footprint and the satisfaction level, we have calculated the Happiness Index of 0.68 (in a 0 to 10 scale). Both the quantitative and the qualitative data have been gathered between January to December, 2008. After the analysis of the results of the Ecological Footprint: 0.433 gha/per capita and the Biocapacity: 6.34 gha/per capita, the settlement can be considered ecologically sustainable and we can say it presents a confirmed ecological superavit.